Pengaruh Rebranding, Persepsi Kualitas, dan Brand Image Terhadap Loyalitas Konsumen pada PT. Cipta Giri Sentosa. - Awwaliyah, Nurul Aini Al; Krisnawati, Wenti; Saepuloh, Asep (VISA: Journal of Vision and Ideas, 2024)
This study aims to analyze the influence of Rebranding, Preceived Quality, and Brand Image on Consumer Loyalty at PT. Copyright Giri Sentosa. This study used quantitative research with 100 respondents. Purposive sampling data sampling technique was collected through 100 respondents. This study used primary data obtained from the distribution of questionnaires online. The respondents were patients of Semen Gresik Hospital who had or are using CGS Drug Delivery Service. Then, non-probability sampling is used for sampling. In this study, it was found that there was a positive and significant influence between Quality Perception and Brand Image on Consumer Loyalty, while Rebranding had a positive but not significant influence on consumer loyalty. The results showed that the Rebranding (X1) has an insignificant effect on the variable of consumer loyalty (Y), this shows that respondents are more likely to prioritize the quality of products or services rather than just changes in the company's visual identity so that these changes do not guarantee consumers to be loyal to CGS drug delivery services. Quality perception variable (X2) has a significant effect on consumer loyalty variable (Y), This shows that the quality provided by CGS matches or even exceeds their expectations thus, making consumers give high value to the quality of service and consumers become loyal. Brand Image variable (X3) has a significant effect on Consumer loyalty variable (Y), This shows that CGS drug delivery service customers tend to have a positive perception of the CGS brand so, this can have a positive impact on customer loyalty., The conclusion is that the Rebranding variable has a positive but not significant effect, while the quality perception and Brand Image variables have a positive and significant effect.